Retention Rates in New Contact Lens Wearers. (September 2018) - Sulley, Anna; Young, Graeme; Hunt, Chris; McCready, Sarah; Targett, Marie-Therese; Craven, Ruth
Abstract : Purpose: To determine the retention rate (RR) for neophyte patients fitted with contact lenses (CLs) and to identify factors associated with retention and dropout. Method: This multisite, sponsor-masked registry study evaluated the 1-year status of neophyte CL wearers fitted in a representative range of UK practices. A total of 26 UK investigational sites each recruited up to 89 neophyte patients. The participants were requested to complete surveys at 1 month (±1 week from date of fitting), 3 months (±2 weeks), and 12 months (±3 weeks) online or through phone. Participants were contacted by email (or phone) and invited to complete an online survey that asked a range of questions regarding their CL wearing experience. Results: Of the 531 participants recruited, 65.3% (347/531) responded to at least one follow-up survey and 42.3% (225/531) responded to all three surveys. One in four patients showed discontinued CL wear by 12 months. Based on evaluable subjects at 12 months, the RR was 77.6% (194/250, 95% confidence interval: 72.0–82.3). The most common reason for discontinuation was problems with vision (41%), followed by discomfort (36%) and handling problems (25%). The factors affecting first-year RRs: sex, spherical refraction, lens usage (full time or part time), and supply method (collected or posted). Conclusions: In this prospective study, the first-year RR for neophyte CL wearers was 77.6%. This was consistent with that noted in a retrospective study: 74.0%. As with the previous study, the commonly cited reason for discontinuation was visual problems.